ANALISIS EFEKTIVITAS FLIGHT OPERATION QUALITY ASSURANCE (FOQA) TERHADAP PENINGKATAN KESELAMATAN PENERBANGAN - MARSA, JAYARDI MAULANA; SUNGKONO, SUNGKONO; WIDANA, IDK KERTA; SUSILO, TRI; ARDIANTO, YUNUS (Universitas Dirgantara Marsekal Suryadarma, 2024)
In 2008, the International Civil Aviation Organization (ICAO), an international aviation authority under the United Nations (UN), amended the aviation safety document. The substance of the amendment was to introduce Flight Operation Quality Assurance (FOQA) as a tool that is a development of the Safety Management System (SMS). The main purpose of FOQA is to collect and process technical data on a flight, measure risks, and estimate possibilities that could jeopardize the safety of a flight. In Indonesia, FOQA has begun to be applied to several flight operators, and one of them is PT XXX. The level of flight safety can be calculated using FOQA. There are a number of events that can be grouped as contributing events of an event and compared to the number of flights in a certain period. The implementation of FOQA can be said to be effective with a significant decrease in the ratio to total flight value from 2019 to 2022 by 45,56%.